Imagery Rescripting on Guilt-Inducing Memories in OCD: A Single Case Series Study - Tenore, Katia; Basile, Barbara; Cosentino, Teresa; De Sanctis, Brunetto; Fadda, Stefania; Femia, Giuseppe; Gragnani, Andrea; Luppino, Olga I.; Pellegrini, Valerio; Perdighe, Claudia; Romano, Giuseppe; Saliani, Angelo M.; et al. (Frontiers in Psychiatry, 2020)
Background and objectives: Criticism is thought to play an important role in obsessive-compulsive disorder (OCD), and obsessive behaviors have been considered as childhood strategies to avoid criticism. Often, patients with OCD report memories characterized by guilt-inducing reproaches. Starting from these assumptions, the aim of this study is to test whether intervening in memories of guilt-inducing reproaches can reduce current OCD symptoms. The emotional valence of painful memories may be modified through imagery rescripting (ImRs), an experiential technique that has shown promising results. Methods: After monitoring a baseline of symptoms, 18 OCD patients underwent three sessions of ImRs, followed by monitoring for up to three months. Indexes of OCD, depression, anxiety, disgust and fear of guilt were collected. Results: Patients reported a significant decrease in OCD symptoms. The mean value on the Yale−Brown Obsessive Compulsive Scale (Y-BOCS) changed from 25.94 to 14.11. At the three-month follow-up, 14 of the 18 participants (77.7%) achieved an improvement of ≥ 35% on the Y-BOCS. Thirteen patients reported a reliable improvement, with ten reporting a clinically significant change (reliable change index = 9.94). Four reached the asymptomatic criterion. Clinically significant changes were not detected for depression and anxiety. Conclusions: Our findings suggest that after ImRs intervention focusing on patients’ early experiences of guilt-inducing reproaches there were clinically significant changes in OCD symptomatology. The data support the role of ImRs in reducing OCD symptoms and the previous cognitive models of OCD, highlighting the role of guilt-related early life experiences in vulnerability to OCD.